The Transition from First to Second Language Instruction: South African Year 4 Learners - Le Roux, Mia; Geertsema, Salomé; Milton, Carmen; Alet Graham, Marien; Wittstock, Kate; Gardee, Humayra; Sattar Carrim, Diyaanah; Veerasamy, Helene (Revista de Investigación en Logopedia, 2025)
The precursor literacy skills phonological and phonemic awareness play a central role in later literacy skills acquisition, especially during the transition from first language to second language mode of learning and teaching. Various research projects in South Africa found that English second language learners, even those who receive instruction in English from Year 0, do not have sufficient precursor and later literacy skills to support academic requirements. Learners who transfer from first-language instruction to second-language instruction in Year 4 may have even lower skills due to less exposure to the medium of instruction (English) on an academic level. This may further influence their literacy abilities. This study intended to analyse and determine the association of precursor literacy and later literacy skill competency measures of Year 4 learners who have recently transitioned from being taught in their L1 to English as their language of learning and teaching (LoLT). A quantitative, cross-sectional, descriptive, and correlational design was used. Non-probability, convenient sampling was employed. Results indicated that participants had limited precursor literacy and later literacy skills in English, demonstrating that transferring to their second language as the language of learning and teaching in Year 4 may be challenging. These challenges impact literacy skills necessary for academic success. Additionally, strong positive correlations between precursor and literacy skills assessed were determined.  Therefore, intervention is essential to equip learners with strong literacy skills in the language of learning and teaching.
Keywords: First language instruction; Literacy skills; Phonological awareness; Second language instruction; South Africa